Potential risk factors for peripheral neuropathy in patients with type 2 diabetes mellitus: a case control study from central Rajasthan - Patel, Govind R.; Samaria, Anil; Kant, Chandra; Prajapati, Gopal R. (International Journal of Advances in Medicine, 2022)
Background: Peripheral neuropathy is one of the most common and debilitating but preventable complications of diabetes mellitus, with significant morbidity as it often leads to foot ulceration and amputation. Therefore, this study was aimed to identify the potential risk factors for diabetic peripheral neuropathy (DPN) which can affect its progression. Methods: This case-control study was conducted on 240 patients with type 2 diabetes mellitus which included 120 patients with clinical evidence of DPN as cases and 120 patients without clinical evidence of DPN as controls. DPN was assessed clinically by neuropathic symptoms and neurological examination using 10 g 5.07 Semmes–Weinstein monofilament and vibration digital biothesiometer. Data regarding presence of potential risk factors were collected from all participants and analyzed using logistic regression analysis to measure an association with DPN. Results: A significant and independent association of advancing age, longer duration of diabetes, hyperglycemia, poor glycemic control, autonomic neuropathy and retinopathy with DPN (p<0.05) was observed. Hypertension, dyslipidemia, smoking, gender, body mass index, method of diabetes control and angiotensin converting enzyme inhibitor usage were not found be associated with DPN. Conclusions: Since hyperglycemia and poor glycemic control were only modifiable risk factors for DPN, intensive glycemic control and primary prevention are the cornerstones for reducing the incidence or slowing the progression of neuropathy and improving quality of life in diabetic patients.